(3RHOI GdHjGf aj HQGgjf CMcGe GdbQBf hJaSjQ BjGJ CMcGe GdbQBfs - (3GdCQOHjdj, CMeO Hf eMeO, J (B993 (3g`s ((3SdjeGf GdMdjs)
(3ChdgG (B:s
(3HSe Gddg (B... (3GYde Cf gGgfG aGFOI dGHO bHd GdTQhY aj GdebUhO ef GdETGQI EdjgG hgj Cf GdeTghQ Hjf GdWdHI Cfg dG jLhR JaSjQ GdbQBf HZjQ fU Ch CKQ MJi bGd GdTjN CHh Ydj GdWHQSj (B...s
(3BNQgG (B:s
.. (3JQc gPg GdBjI aj BjGJ GdCMcGe aj cfR GdYQaGf SHH GdfRhd hchfgG ebUhQI Ydjge ceG aYdg (B... (3YQaJ Cfg djS HLjO heKd gPG CaYd aj cKjQ ef GdBjGJ MjK YeJ eY chf SHH GdfRhd NGUG (B.. (3aJCeds
(3bHdgG ahGFO eJaQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B1/ 234s
(3GdPQjYI (B12\126s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJaSjQ hYdhe GdbQBfs